An investigation of media Ruangguru as educational online platform in studying English - Cut Raisa Prillya; Sofyan A. Gani; Saiful Marhaban (Universitas Syiah Kuala, 2021)
Ruangguru is one of the educational online platforms that has existed in Indonesia since 2014. The application which focused on education-based services became the new phenomenon of online learning that attracted students’ attention, especially in this 4.0 era. Thus, the main objective of this research was to investigate the use of the medium Ruangguru as an educational online platform and the student's perspective on the use of Ruangguru in learning English. The sample of the study was 10 students in the ninth grade at SMP IT Nurul Ishlah Banda Aceh. The data were collected and analyzed by using a descriptive qualitative design. The results showed that the students felt convenient in using Ruangguru, for the reason that it could be accessed through mobile phone anytime and anywhere. Based on the students’ perspective, Ruangguru was quite interesting and it could attract students’ attention in learning English for the reason that it provided visual animation which made the learning atmosphere became fun. The results of the study were expected to become a reference for school practitioners, parents, students, and general readers to find the learning aids that are compatible with the sophistication of technology and information update in learning English.